Perbedaan Tingkat Keberhasilan Servis Permainan Bolavoli Antara Elite Atlet Pelajar Tim Indonesia dan Tim Filipina Pada Pertandingan ASEAN School Games Ke 11 Tahun 2019 (Indonesian Journal for Physical Education and Sport, 2021)
This study aimed to determine the differenca in the level of succes of the volleyball game service between the elite athletes of the Indonesian team ASEAN School Games in 2019.The method of this study used aqualitative case study approach, and the research subjects were elite athletesof Indonesian team and team Philippines.The numbered 48 athletes.The research instrument used a check-list (observation method) and documentation method.The data analysis technique used descriptive percentages.The results of this study included positions attacked by the Indonesian men’s team service position six as many as 154 (41.88%) jump serve 178 (41.85%), Indonesian women’s team position six as many as 115 (46.96%), floating serve 123 (42.68%), men’s Filipino team position five as many as 124 (47.58%), jump floating serve 235 (46.60%), Filipino women’s team position 6 182 (46.70%), jump floating serve 278 (49.46%).Recapitulation of male Indonesian team services 60.45% good category, Indonesian women’s team 48.08% enough category, men’s Philipines team 43.23% enough category, Philipines women’s team 46.96% enough category.More effective service for the men’s team is more useful for the Indonesian men’s team, and the women’s team is more useful for the Indonesian women’s team.The results of this study are positions that are often attacked by Indonesian teams and Filipino teams positions 5 and 6.The types of service used by Indoneisan team and the Filipino team are floating serve, jump floating ser e, jump serv.More effective service are used both male and female teams more effectively in Indonesian.